The Effect of Age on Fracture Risk: A Population-Based Cohort Study - Wenbin Liang; Tanya Chikritzhs (Journal of Aging Research)
Aim. To precisely estimate the effect of age on the risk of fracture hospitalisation among the Western Australia population over the life course. Methods. This population-based cohort study used hospital data on fractures for the period January 1991 to January 2013 among Western Australians born between 1915 and 1990. Results. The average incidence rates (per 10,000 person-years) of fracture hospitalisation (95% confidence interval) were 50.12 (49.90, 50.35), 55.14 (54.82, 55.48), and 45.02 (44.71, 45.32) for both males and females, males only, and females only, respectively. The age-specific rate of fracture hospitalisation (in natural logarithm form) in adults (>18 years) was well predicted by age at its 1st, 2nd, and 3rd power in males with an adjusted R-squared of 0.98 and p<0.001. For females, the trend was also well predicted by its 1st and 2nd powers (the 3rd power term of age was removed due to its p value > 0.8) with an adjusted R-squared of 0.99 and p<0.001. Conclusions. Overall trends in age and gender specific risk of fracture among the Western Australian population were similar to estimates reported from previous studies. The trend in fracture hospitalisation risk over the life course can be almost fully explained by age.